SOCIAL WORK, ELEMENTARY DEVELOPMENT, LITERACY - Dorschkly, Lilo (Socialinė teorija, empirija, politika ir praktika, 2009)
Since a couple of years in Germany numerous publications appeared on problems of education in connection with social work. Profound changes in the occupational system have led to the emergence of new standards of basic skills and educational requirements. "Lifelong Learning"  as a  political  attempt  to  cope with these  changes includes  expansion  and  transgression  of  traditional  and organized learning. Not surprising that professional social work is confronted with several problems concerning these changes. The main task of this essay is to show how education as a social workers business can become highly ambivalent due to essential discrepancies between functional and emancipatory conceptions of education. Discussing the advancement of literacy/reading and writing skills this article shows that social work has to develop its own educational approaches to avoid adopting rules and functions of the organized educational system.
Keywords: Occupational system; Policy; Social work; Education; Primary education